Baicalein, Ethyl Acetate, and Chloroform Extracts of Scutellaria baicalensis Inhibit the Neuraminidase Activity of Pandemic 2009 H1N1 and Seasonal Influenza A Viruses. (20th June 2013) - Hour, Mann-Jen; Huang, Su-Hua; Chang, Ching-Yao; Lin, Yen-Kuan; Wang, Ching-Ying; Chang, Yuan-Shiun; Lin, Cheng-Wen
Abstract : This study rated antiviral activity of Scutellaria baicalensis Georgi ( S. baicalensis ) extracts against influenza A virus subtypes, for example, pandemic 2009 H1N1, seasonal H1N1 and H3N2. Ethyl acetate (EtOAc) and chloroform extracts inhibited in vitro neuraminidase (NA) enzymatic activity and viral replication more than methanol (MeOH) extract. EtOAc extract demonstrated NA inhibition IC50 values ranging from 73.16 to 487.40 μ g/mL and plaque reduction IC50 values ranging from 23.7 to 27.4 μ g/mL. Chloroform extract showed antiviral activities with plaque reduction IC50 values ranging from 14.16 to 41.49 μ g/mL Time-of-addition assay indicated that EtOAc and chloroform extracts also significantly inhibited virus yields after infection. HPLC analysis demonstrated that baicalin was dominant in the MeOH extract; baicalein and chrysin were rich in the EtOAc and chloroform extracts. Molecular simulation revealed baicalein hydrogen bonding with Glu277 as well as hydrophobic and Van der Waals interactions with Ile222, Arg224, Ser246, and Tyr347 in NA1 active sites of NA1. Baicalein inhibited in vitro replication of influenza A viruses pandemic 2009 H1N1 (IC50  = 0.018 μ M) and seasonal 2007 H1N1 using plaque reduction assays. A combination of low-dose baicalein with other anti-influenza agents could be applicable for development of alternative remedies treating influenza A virus infection.